2007
DOI: 10.1556/aalim.36.2007.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of glucosinolates in some raw and processedBrassicavegetables grown in Croatia

Abstract: The interest in food with chemoprotective properties has been steadily increasing due to many epidemiological studies indicating the lower probability of acquiring some kinds of cancer (e.g. colon, prostate, breast, cervical) in populations, whose diet includes large quantities of Brassica vegetables. The biologically active compounds in Brassica vegetables are the breakdown products of glucosinolates, including isothiocyanates, nitriles, thiocyanates, indoles and oxazolidinethiones from which indoles and isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…Aerial parts (flower, leaf and stem) contain four Met-derived GSLs and four Trp-derived GSLs ranging from 0.07 to 3.86 μmol/g DW and 0.73 to 2.57 μmol/g DW, respectively. These GSLs were previously reported in the leaves of the fresh collard investigated [ 8 , 9 ] as well as in other types of kale [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. The stem was also shown to contain minor quantities of two Phe-derived GSLs.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Aerial parts (flower, leaf and stem) contain four Met-derived GSLs and four Trp-derived GSLs ranging from 0.07 to 3.86 μmol/g DW and 0.73 to 2.57 μmol/g DW, respectively. These GSLs were previously reported in the leaves of the fresh collard investigated [ 8 , 9 ] as well as in other types of kale [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. The stem was also shown to contain minor quantities of two Phe-derived GSLs.…”
Section: Resultssupporting
confidence: 82%
“…Compared to other Brassica vegetables (such as cabbage, Brussels sprouts, broccoli, and cauliflower, for example), collard has not been the subject of as much research [ 8 ]. These studies included fresh collard leaves, in which the most prevalent GSLs were indolic ones, i.e., indol-3-ylmethyl GSL (glucobrassicin, 43 ), followed by 4-hydroxyindol-3-ylmethyl GSL (4-hydroxyglucobrassicin, 28 ), 4-methoxyindol-3-ylmethyl GSL (4-methoxyglucobrassicin, 48 ), and N -methoxyindol-3-ylmethyl GSL (neoglucobrassicin, 47 ), together with aliphatic GSLs ( R S )-3-(methylsulfinyl)propyl GSL (glucoiberin, 73 ) and allyl GSL (sinigrin, 107 ) [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The high level of glucobrassicin might facilitate explaining the fact that 'Dania' no longer is in use, as this glucosinolate has been associated with the perceived bitter taste of Brassica vegetables, thus being unfavorable concerning consumer acceptability (Schonhof et al, 2004). In general, the types and levels of indole GLS correspond to what others have found (Cie slik et al, 2007;Delonga, Redovniković , Dragović -Uzelac, Mrkić , & Vorkapić -Furač, 2007;Nilsson et al, 2006;Schonhof et al, 2004;Sones et al, 1984b;Tian et al, 2005).…”
Section: Glucosinolatesmentioning
confidence: 68%
“…Delonga et al [31] obtained higher amounts of GLS sum, whilst lower values were reported by Mithen et al [32] as well as Song and Thornalley [12].…”
Section: Gls Content In Raw Vegetablesmentioning
confidence: 75%